Talking points in mathematics - Straker, Anita (New York : Cambridge, 1998)
This text contains suggestions for encouraging children to think and talk about mathematics. The ideas are grouped by topic and arranged in rough order of difficulty, ranging from National Curriculum level 1 to 6
Keywords: Mathematics -- Study and teaching (Elementary)